PENERAPAN MULTI-MIKROKONTROLER PADA MODEL ROBOT MOBIL BERBASIS LOGIKA FUZI - Nuryono Satya Widodo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
This paper proposed a fuzzy logic based mobile robot as implemented in a multimicrocontroller system. Fuzzy logic controller was developed based on a behavior based approach. The Controller inputs were obtained from seven sonar sensor and three tactile switches. Behavior based approach was implemented in different level priority of behaviors. The behaviors were: obstacle avoidance, wall following and escaping as the emergency behavior. The results show that robot was able to navigate autonomously and avoid the entire obstacle.